Have we hit a wall with whole kidney decellularization and recellularization: A review. (December 2021) - de Haan, Marlon J.A.; Witjas, Franca M.R.; Engelse, Marten A.; Rabelink, Ton J.
Abstract: The purpose of organ decellularization is to remove all cellular components whilst preserving the extracellular matrix (ECM). It has been hypothesized that this decellularized ECM can be used as a scaffold for the development of personalized bioengineered kidneys by repopulating it with patient-derived cells. The renal artery, vein, and ureter are most frequently used for whole kidney repopulation. Cell perfusion through the artery and vein enables revascularization of decellularized kidneys. However, adequate repopulation of the epithelial compartment remains unattainable. Although it has become unlikely that recellularized whole kidneys will be the solution to reduce donor organ shortages within the foreseeable future, advances made within the field of whole organ decellularization and recellularization have paved the way for alternatives that actually may help to solve these shortages. This includes ex vivo refurbishment and personalization of discarded donor organs during machine perfusion. Graphical abstract: Image 1 Highlights: Whole kidney decellularization enables the production of tissue-specific scaffolds. Decellularization paradox: cell removal versus ECM preservation. Revascularization of human decellularized kidneys is feasible. Repopulation of epithelial compartment is impaired by preserved basement membrane. Prolonged ex vivo organ perfusion provides new perspectives.